2019
DOI: 10.1186/s13104-019-4217-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contaminants of stored blood and blood components ready for transfusion at blood banks in Mekelle, Northern Ethiopia

Abstract: ObjectiveBacterial contamination of donated blood and blood components is a major public health problem globally. The aim of the study was to evaluate the rate and spectrum of bacterial contaminations and antimicrobial susceptibility pattern of contaminants in stored blood and blood components.ResultsA total of 196 blood and blood components (concentrated red blood cells, fresh frozen plasma, and platelets) were included. Bacterial contamination was observed in 18 (9.2%) of the blood and blood components, of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…18 Sehgal et al, reported a positive bacterial culture in 5.38% of platelet concentrates in PRP, while another research conducted in a blood bank in Ethiopia showed a very high bacterial contamination rate in 4 platelet bags out of a total of 12 bags tested. 19,20 Our results were similar to those reported in a Moroccan blood bank which analyzed platelet concentrates over seven years and reported culture positivity of 0.44%. 21 Bacterial contamination screening was introduced in Australian blood banks in 2008, and researchers have demonstrated a decline in the initial machine culture positivity rate in platelet concentrates of 0.6% since 2013.…”
Section: Discussionsupporting
confidence: 88%
“…18 Sehgal et al, reported a positive bacterial culture in 5.38% of platelet concentrates in PRP, while another research conducted in a blood bank in Ethiopia showed a very high bacterial contamination rate in 4 platelet bags out of a total of 12 bags tested. 19,20 Our results were similar to those reported in a Moroccan blood bank which analyzed platelet concentrates over seven years and reported culture positivity of 0.44%. 21 Bacterial contamination screening was introduced in Australian blood banks in 2008, and researchers have demonstrated a decline in the initial machine culture positivity rate in platelet concentrates of 0.6% since 2013.…”
Section: Discussionsupporting
confidence: 88%
“…Bacterial culture, pathogen reduction (PR) and point of release testing were methods being considered for implementation by members. Several other small studies reported the prevalence of bacterial contamination of blood and blood components using cultures on different media, in which isolates were identified using standard biochemical and bacteriological methods [15, 16]. Research, surveillance and implementation of interventions in lower‐income countries at present lags that of high‐income countries (Box 1).…”
Section: The Problem: Strsmentioning
confidence: 99%
“…Furthermore, susceptibility to microorganisms and viral contamination remains a long-standing issue for polymers, with 7.5% of patients experiencing healthcare-associated infections associated with surgeries and biomedical devices in Canada, , and 50 000+ lives are lost across the United States and Europe due to multidrug-resistant microorganisms. Furthermore, blood storage contamination affects 0.2% of stored blood bags in the United States and in higher rates in undeveloped countries . Therefore, developing PVC surfaces with improved antimicrobial properties is a real need …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, blood storage contamination affects 0.2% of stored blood bags in the United States and in higher rates in undeveloped countries. 12 Therefore, developing PVC surfaces with improved antimicrobial properties is a real need. 13 The research on PVC's surface modification is an active field and has common goals: increased biocompatibility, eradicate pathogens, and not trigger an adverse response, e.g., blood coagulation.…”
Section: ■ Introductionmentioning
confidence: 99%